Identical twins carry a persistent epigenetic signature of early genome programming - Jenny van Dongen (Nature Portfolio, 2021)
The mechanisms underlying how monozygotic (or identical) twins arise are yet to be determined. Here, the authors investigate this in an epigenome-wide association study, showing that monozygotic twinning has a characteristic DNA methylation signature in adult somatic tissues.